2013
DOI: 10.1371/journal.pone.0075340
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimuli Are Anti-Apoptotic in Skeletal Muscle via Extracellular ATP. Alteration of This Signal in Mdx Mice Is a Likely Cause of Dystrophy

Abstract: ATP signaling has been shown to regulate gene expression in skeletal muscle and to be altered in models of muscular dystrophy. We have previously shown that in normal muscle fibers, ATP released through Pannexin1 (Panx1) channels after electrical stimulation plays a role in activating some signaling pathways related to gene expression. We searched for a possible role of ATP signaling in the dystrophy phenotype. We used muscle fibers from flexor digitorum brevis isolated from normal and mdx mice. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 75 publications
2
28
0
Order By: Relevance
“…In addition to de novo expression of Cxs 39, 43 and 45, mdx myofibers showed upregulation of Panx1 channels and de novo expression of two other non-selective membrane channels, P2X 7 R and TRPV2, as described previously [16,17,19]. Notably, the absence of Cx43/Cx45 expression by mdx fibers abrogated the expression of TRPV2 as observed by western blots and immunofluorescence assays, suggesting that TRPV2 expression is controlled downstream of Cx43/Cx45 expression.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition to de novo expression of Cxs 39, 43 and 45, mdx myofibers showed upregulation of Panx1 channels and de novo expression of two other non-selective membrane channels, P2X 7 R and TRPV2, as described previously [16,17,19]. Notably, the absence of Cx43/Cx45 expression by mdx fibers abrogated the expression of TRPV2 as observed by western blots and immunofluorescence assays, suggesting that TRPV2 expression is controlled downstream of Cx43/Cx45 expression.…”
Section: Discussionsupporting
confidence: 71%
“…and improves muscle performance [16]. Muscles of mdx mice also show upregulation of pannexin1 (Panx1) channels [17] and purinergic ionotropic P2X 7 receptors (P2X 7 Rs) [18,19]. The possible relevance of at least of Panx1 channels in the muscle pathogenesis has been ruled out [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been obtained using heart homogenates from mdx mice (Gonzalez, Ramachandran, Xie, Contreras, & Fraidenraich, ). Despite this, Panx1 levels were elevated in triad‐enriched fractions (T‐tubule/sarcosplasmic reticulum junctional complexes) from back and limbs muscles of mdx mice (Valladares et al, ), suggesting that the effect of dystrophy on Panx1 levels may differ amongst muscle type. Accordingly, Panx1 levels were significantly reduced in EDL and SOL muscles as well as in the diaphragm of dKO mice, but not in TA muscles.…”
Section: Discussionmentioning
confidence: 99%
“…While ATP release has been demonstrated to have an anti‐apoptotic effect in normal fibers, exogenous ATP induced an increase in the expression of pro‐apoptotic genes in dystrophic fibers, which could contribute to fiber loss in DMD (Valladares et al, ). Interestingly, dystrophin has been identified as part of the multiprotein complex with Panx1 involved in excitation‐transcription coupling, which was found to be altered in mdx muscle fibers (Valladares et al, ). While deregulation of Panx1 channel activity may not be linked to heart failure in DMD as treatment with 10 Panx did not affect the isoproterenol‐induced lethality in mdx and dKO mice (Gonzalez et al, ), Panx1 channels may still be involved in the muscle fragility, reduced muscle strength, contraction‐induced damage, and fiber necrosis or fiber loss seen in DMD.…”
Section: Discussionmentioning
confidence: 99%
“…4 Initially, EMS was introduced as training program tool to improve muscular strength, but it is now used for muscle rehabilitation, treat obesity and improve body shape. 5,6 EMS has been suggested to promote the formation of adenosine triphosphate, 7 increase oxygen intake, 8 decrease body fat by increasing muscle strength, improve blood circulation, accelerate waste product excretion though the lymphatic system, 5 stimulate cell regeneration, 9 and increase metabolic rate by increasing local temperature. 10 Although a previous clinical trial reported reduced waist circumference (WC) after 8 weeks of EMS, 11 unfortunately, no randomized controlled trial has evaluated the effect of EMS on obesity or regional fat distribution.…”
Section: Introductionmentioning
confidence: 99%